Estimation of fatigue crack growth behavior for small-sized C-shaped inside edge-notched tension (CIET) specimen using compliance technique. (December 2015) - Bao, C.; Cai, L.X.; Dan, C.
Graphical abstract: Highlights: A new small-size CIET specimen is developed for fatigue crack growth rate tests. Compliance technique for CIET specimen is constructed. A crack closure model is introduced to eliminate the difference of test results. Abstract: Being restricted by the relative larger size requirement, traditional and standard fracture specimens are not applicable for the estimation of fatigue crack growth behavior of some very finite-sized components and precious materials. This study develops a small-sized C-shaped inside edge-notched tension (CIET) specimen which has an advantage of specimen minimization and a wide range of adaptability. A systemic compliance technique for estimating fatigue crack growth behavior of CIET specimen has been successfully constructed and experimentally verified. Groups of fatigue crack propagation rate tests of both CIET specimen and CT specimen for 5083-H112 aluminum alloy were carried out. The resulted da / dN  ∼ Δ K curves are heavy affected by specimen configuration and load ratio, and the difference between these da / dN  ∼ Δ K curves has been successfully removed by introducing the correction of plasticity-induced crack closure effect. Consequently, the feasibility of CIET specimen for estimating fatigue crack propagation behavior for small-sized components and precious materials has been evidently confirmed.